Does receiving advice from Voter Advice Applications (VAAs) affect public opinion in deeply divided societies? Evidence from a field experiment in Northern Ireland. (November 2019) - Garry, John; Tilley, James; Matthews, Neil; Mendez, Fernando; Wheatley, Jonathan
Despite the global growth in the use of Voter Advice Applications (VAAs), which advise users on how similar their own policy views are to the policy positions of the political parties, there have been few field experiments that isolate the causal effects of VAA use on party support. Nor has there been much investigation of how VAAs may help to ameliorate ethnically based voting divisions by refocusing voter attention on other issues. This article draws on evidence from a field experiment in the deeply divided context of Northern Ireland. We find that at the individual level party preferences are somewhat more closely related to voter ideology after the provision of advice. Yet, at the aggregate level, we find no evidence that advice leads to weaker ethno-national structuring of party support. These results suggest that while receiving advice from VAAs has some impact on users' party preferences, there is no observable overall impact on support levels for the ethno-national blocs in Northern Ireland.